2007
DOI: 10.1080/10408390600919056
|View full text |Cite
|
Sign up to set email alerts
|

Cereal Non-Cellulosic Polysaccharides: Structure and Function Relationship—An Overview

Abstract: The non-cellulosic polysaccharides present in cereals (2-8%) are mostly arabinoxylans, (1 --> 3),(1 --> 4)-beta -glucans, pectins and arabinogalactans. Of these, the arabinoxylans are known to absorb large amounts of water and influence significantly the water balance, rheological properties of dough, and the retrogradation of starch and bread quality. (1 --> 3),(1 --> 4)-beta -glucans are known as biological response modifiers (BMS) as they are believed to modulate the immune response. Cereal Pectins and arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 61 publications
0
45
0
1
Order By: Relevance
“…4, indicated that the cell survival in 30% malt extract was higher compared to that in supplemented wheat and barley extracts, verifying the above hypothesis. The compounds responsible for the increased protection of malt extract could be oligosaccharides and dietary fibers, which are found to be present in malt; however the information regarding their exact structures is limited (Han, 2000;Henry, 1988;Muralikrishna & Rao, 2007). Nevertheless, this type of compounds, such as raffinose and dietary fibers derived from legumes, cereals or fruits, have been suggested to influence probiotic survival in various products (Martinez-Villaluenga, Frias, Gomez, & Vidal-Valverde, 2006;Saarela, Virkajarvi, Nohynek, Vaari, & Matto, 2006;Sendra et al, 2008).…”
Section: Resultsmentioning
confidence: 96%
“…4, indicated that the cell survival in 30% malt extract was higher compared to that in supplemented wheat and barley extracts, verifying the above hypothesis. The compounds responsible for the increased protection of malt extract could be oligosaccharides and dietary fibers, which are found to be present in malt; however the information regarding their exact structures is limited (Han, 2000;Henry, 1988;Muralikrishna & Rao, 2007). Nevertheless, this type of compounds, such as raffinose and dietary fibers derived from legumes, cereals or fruits, have been suggested to influence probiotic survival in various products (Martinez-Villaluenga, Frias, Gomez, & Vidal-Valverde, 2006;Saarela, Virkajarvi, Nohynek, Vaari, & Matto, 2006;Sendra et al, 2008).…”
Section: Resultsmentioning
confidence: 96%
“…15 Cereal, the source material of straw, also contains arabinogalactan, suggesting that exposure to this plant-derived oligosaccharide might protect children against asthma and atopy. 16 Alternatively or additionally, thus far unidentified microbial exposures associated with hay and straw might explain the effect. Straw has been shown to be contaminated with a high variety of fungi and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Murlikrishna and Subba Rao (2007) have reviewed work on cereal non-cellulosic polysaccharides with special reference to the recently characterized finger millet arabinoxylans.…”
Section: O-acetyl Galactoglucomannansmentioning
confidence: 99%